Online Research Supervision and its Influence Among Health Professional Students and Research Supervisors during Covid-19 Pandemic; An Evaluation Study of Clarke International University - Atim , Fiona; Lulu M. , Patrick; Lubanga , Robert; Githinji , Florence (African Journal of Education,Science and Technology (AJEST), 2022)
The COVID-19 pandemic which hit most nations in 2020 has triggered several changes in the education system. For example, students in higher institutions of learning in Uganda have had to adjust to online learning amidst scarce resources. The study evaluated how online research supervision has influenced self-learning among health professional students at Clarke International University. An analytical cross-sectional study design was employed among 150 students conducting research and 08 Key informants holding administrative positions and supervisory roles were interviewed. Quantitative data was collected using a questionnaire administered through a semi-structured google survey form. Univariate, bivariate, and multivariate analysis conducted using SPSS (20.0) and ATLAS Ti for analyzing qualitative data. The majority 106 (70.7%) of the respondents were satisfied with online research supervision. The findings were influenced by; age of respondents (p=0.690), knowledge on application of online tools (aOR=2.580, 95% CI=0.243-27.406, P=0.432), supervisors’ availability for consultation (p=0.996), availability of e-resources for research (p=0.995) and support from other departments (aOR=4.524, 95%CI=0.167-122.535, P=0.370). Online research supervision is possible. Most of the students were able to apply knowledge gained in research methodology class, although there is need for readily available supervisors and provision of timely feedback. Institutions should focus on providing more e-resources, and continuous training and awareness among students and supervisors to improve online research supervision. Keywords: